DETERMINAN INTERNAL KEMAMPULABAAN PERBANKAN INDONESIA (STUDI EMPIRIS PADA PERBANKAN UMUM KONVENSIONAL YANG TERDAFTAR DI BEI TAHUN 2011-2016) - Cindy, Cindy (Jurnal Muara Ilmu Ekonomi dan Bisnis, 2018)
The purpose of this research is to analyze and prove empirically the quality of productive assets (NPL), firm size (Ln total assets), liquidity (LDR), capital adequacy (CAR), and efficiency (BOPO) as an internal determinant of profitability with the indicator RoRWA and ROA bank in Indonesia. Samples taken for 31 banks listed on the Indonesia Stock Exchange for Conventional Comercial Banks in Indonesia for the period 2011-2016. Data analyzed using Structural Equation Modelling (SEM) with software SmartPLS version 2.0. The results of this study indicate the quality of productive assets, firm size, and capital adequacy have a positive effect on profitability, while liquidity and efficiency have a negative affect on profitability.The purpose of this research is to analyze and prove empirically the quality of productive assets (NPL), company size (Natural logarithm of total asset), liquidity (LDR), capital adequacy (CAR), and efficiency level (BOPO) as an internal determinant of profitability with RoRWA and ROA indicators on banks in Indonesia. Samples of 31 banks listed on the Indonesia Stock Exchange for Conventional Commercial Banks in Indonesia year 2011-2016. Data was analyzed using Structural Equation Modelling (SEM) with SmartPLS software version 2.0. The result of this study indicates that the quality of productive assets, company size, and capital adequacy affect profitability positively,while liquidity and efficiency affect profitability negatively.Keywords : Profitability, The Quality of Productive Assets, Firm Size, Liquidity, Capital Adequacy, Efficiency